Надо докажите тождетство 1) (x-y)^2 =(y-x)^2 ; 2) (-b-a)^2 = (a+b)^2

vikatopcheg vikatopcheg    2   17.08.2019 09:50    0

Ответы
Lana0602 Lana0602  05.10.2020 00:34
1
(x-y)²=x²-2xy+y²
(y-x)²=y²-2xy+x²
x²-2xy+y²=y²-2xy+x²
2
(-b-a)²=b²+2ba+a²
(a+b)²=a²+2ab+b²
b²+2ba+a²=a²+2ba+b²
ПОКАЗАТЬ ОТВЕТЫ
ViKtOrIaSmIrNoVa2007 ViKtOrIaSmIrNoVa2007  05.10.2020 00:34
(x-y)^2=(y-x)^2 \\ x^2-2xy+y^2=y^2-2xy+x^2
что и требовалось доказать

(-b-a)^2=(a+b)^2 \\ (-b^2)+2(-b)(-a)+(-a)^2=a^2+2ab+b^2 \\ b^2+2ab+a^2=a^2+2ab+b^2
что и требовалось доказать
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра